#### Answer

Point A:
$y=\frac{1}{2}x+3$
$y=\frac{1}{2}(0)+3$
$y=3$
Point B:
$y=\frac{1}{2}x+3$
$y=\frac{1}{2}(-4)+3$
$y=-2+3$
$y=1$
Point C:
$y=\frac{1}{2}x+3$
$0=\frac{1}{2}x+3$
$-3=\frac{1}{2}x$
$x=-6$

#### Work Step by Step

To find the coordinates of Point A and B, substitute the given x-values into the given formula $y=\frac{1}{2}x+3$ to find the y-value for the corresponding x-values.
To find the coordinates of Point C, substitute the given y-value into the given formula $y=\frac{1}{2}x+3$ to find the x-value for the corresponding x-value.
When all three points are found, plot each point on the graph provided and draw a straight line, which represents (graphically) the given formula $y=\frac{1}{2}x+3$ .